Nutritional Aspects and Health Benefits of Bioactive Plant Compounds against Infectious Diseases: A Review. Issue 4 (19th May 2023) - El-Saadony, Mohamed T.; Zabermawi, Nidal M.; Zabermawi, Nehal M.; Burollus, Maryam A.; Shafi, Manal E.; Alagawany, Mahmoud; Yehia, Nahed; Askar, Ahmed M.; Alsafy, Sara A.; Noreldin, Ahmed E.; Khafaga, Asmaa F.; Dhama, Kuldeep; et al.
ABSTRACT: In the current century, the development of medicine and molecular biotechnology led to successful containment and even eradication of some human pathogens, especially in developed countries. However, some pathogens have evolved, resulting in the emergence of other infectious diseases in developed countries. Human socioeconomic activities and the advancement of technology and transportation have led to the quick movement of humans to different parts of the world. There is a significant concern that this movement enhances the distribution of pathogens, making it difficult to contain, as witnessed with the global spread of the 2009 influenza pandemic within only 3 months and the 2014 Ebola outbreak, which spread in various West African countries within 8 months. Natural products obtained from plant sources can be identified as the next-generation antibacterial and antiviral alternatives. In developed countries, 80% of the population depends on traditional medicine for their primary healthcare issues, according to the World Health Organization (WHO). Relatedly, India is one of the highest producing countries for medicinal herbs. It is considered an international botanical garden. Therefore, the focus of this current review was on the importance of using plants to treat bacterial and viral diseases due to the many advantages of these plants.